(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Beef meat is an animal flesh food that is considered a good diet for consumption as it contains many minerals, vitamins, basic amino acids and essential fatty acids. The people prefer marinated beef meat from a few decades. Microbiological count affection food and especially pathogenic organisms of public health importance. The tenderness and flavour considered as the main factors that affect consumer’s acceptability and satisfaction. World’s beef meat production in 2016 is approximately about 321,000,000 tons. The importance of post marinated beef meat on quality and acceptability with the importance of consumer point of view as the health and diet increases as beef meat is a high source of minerals, protein, vitamins as well as some essential compounds. Samples from meat food were collected from supermarkets, Egypt. This study evaluates the effects of marinade on meat microbial quality as reduction of the microbiological count. Microbial count was carried out by using selective medium and to determine the best marinating method. The results indicated that SDS+1% give best microbial controlling buffer where decreasing bacterial and fungal count to around zero that gave marvellous results.